2017
DOI: 10.1038/s41598-017-11554-w
|View full text |Cite|
|
Sign up to set email alerts
|

A Multi-Institutional Comparison of Dynamic Contrast-Enhanced Magnetic Resonance Imaging Parameter Calculations

Abstract: Dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) provides quantitative metrics (e.g. Ktrans, ve) via pharmacokinetic models. We tested inter-algorithm variability in these quantitative metrics with 11 published DCE-MRI algorithms, all implementing Tofts-Kermode or extended Tofts pharmacokinetic models. Digital reference objects (DROs) with known Ktrans and ve values were used to assess performance at varying noise levels. Additionally, DCE-MRI data from 15 head and neck squamous cell carcinoma pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 47 publications
(35 reference statements)
1
12
0
Order By: Relevance
“…Further, Cron et al 20 demonstrated that larger percentages of unphysical values within regions are computed by algorithms when more noise is present in the DCE-MRI images. The inter-algorithm differences and noise dependence are a hindrance to the clinical implementation of DCE-MRI and prompt thorough investigation towards establishing better repeatability and reproducibility between sites before multi-institutional clinical trials of HNSCC patients with DCE-MRI 21 .…”
Section: Background and Summarymentioning
confidence: 99%
“…Further, Cron et al 20 demonstrated that larger percentages of unphysical values within regions are computed by algorithms when more noise is present in the DCE-MRI images. The inter-algorithm differences and noise dependence are a hindrance to the clinical implementation of DCE-MRI and prompt thorough investigation towards establishing better repeatability and reproducibility between sites before multi-institutional clinical trials of HNSCC patients with DCE-MRI 21 .…”
Section: Background and Summarymentioning
confidence: 99%
“…Additionally, acquisition and analysis protocols to reduce uncertainty in the imaging measurements need to be developed. We [ 161 , 162 , 163 ] and others [ 164 , 165 , 166 , 167 ] have begun to demonstrate that quantitative imaging techniques to quantify tissue vascularity can be performed with high accuracy and precision. Furthermore, we have shown that certain MRI measures can be collected with high quality in the community setting (and not in a research or academic setting) using widely available hardware [ 28 ].…”
Section: Future Directionsmentioning
confidence: 99%
“…This challenge calls for the need to devote serious efforts in standardization of the complete process affecting the imaging biomarkers. 223 , 224 , 225 , 226 , 227 …”
Section: Mr Biomarkers Associated Biologic and Genetic Processes And Imaging Techniquesmentioning
confidence: 99%